An investigation of the Rocky Ford water power - Randall, Delmer William (My University, 1899)
Introduction: The rapids known as Rocky Ford are situated on the Big Blue River, four miles, north of Manhattan. A portion of the power had, before the advent of railroads, been used to run a grist and saw mill. The old mill-building still stands in good condition; but the dam, which was a frame structure, became dilapidated thru lack of attention, and was carried away by a freshet, several years since. In an investigation of a water power the first point to consider is the use to which the power is to be applied- in this case the requirements of a central power station. To furnish both light and power a twenty-four-hour plant would be necessary making a water storage impossible, and duplicate machinery a necessity. For light only the plant would need to be in operation but twelve or fifteen hours making a water storage possible. In 1898, Mr. M.W. Sanderson, B. Sc investigated this power with regard to irrigation; and having had no opportunity to consult his work, I do not know, but this may in part, be a repetition.
Citation: Randall, Delmer William. An investigation of the Rocky Ford water power. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Determination of Power; Natural Fall; Artificial Fall; Minimum Flow and Computation of Power; Theses; Manuscripts (documents)